2022
DOI: 10.1172/jci.insight.156013
|View full text |Cite
|
Sign up to set email alerts
|

P. aeruginosa augments irradiation injury via 15-lipoxygenase–catalyzed generation of 15-HpETE-PE and induction of theft-ferroptosis

Abstract: Total body irradiation (TBI) targets sensitive bone marrow hematopoietic cells and gut epithelial cells causing their death and TBI induces the state of immunodeficiency combined with intestinal dysbiosis and non-productive immune responses. We found enhanced Pseudomonas aeruginosa (PAO1) colonization of the gut leading to the host cell death and strikingly decreased survival of irradiated mice. PAO1-driven pathogenic mechanism includes theft-ferroptosis realized via: i) curbing host anti-ferroptotic system GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…For example, Pseudomonas aeruginosa , an opportunistic pathogen commonly habituating in hospitalized immunocompromised patients, induces ferroptosis, augments post-radiation gut barrier breach and ensuing lethality through producing 15-lipoxygenase. 15-lipoxygenase also promotes a transition to pro-inflammatory milieu by modulating inflammation-related lipid signaling, immunocyte recruitment and cytokine production in small intestine [ 52 ].…”
Section: Mechanistic Investigations On Microbiota-host Interactions I...mentioning
confidence: 99%
“…For example, Pseudomonas aeruginosa , an opportunistic pathogen commonly habituating in hospitalized immunocompromised patients, induces ferroptosis, augments post-radiation gut barrier breach and ensuing lethality through producing 15-lipoxygenase. 15-lipoxygenase also promotes a transition to pro-inflammatory milieu by modulating inflammation-related lipid signaling, immunocyte recruitment and cytokine production in small intestine [ 52 ].…”
Section: Mechanistic Investigations On Microbiota-host Interactions I...mentioning
confidence: 99%
“…It was proved that Pseudomonas aeruginosa (PAO1) could stimulate ferroptosis by making PAO1 15-lipoxygenase (pLoxA) act on 15-LOX and GPX4 and significantly reduce the survival of irradiated mice. The application of baicalein, a lipoxygenase inhibitor, reversed this phenomenon and reduced mortality in mice exposed to total body irradiation (TBI) and PAO1 infection ( Dar et al, 2022 ). Polycysteine can improve the survival of mice exposed to TBI and reduce radiation-induced damage by activating GPX4 and inhibiting nicotinamide adenine dinucleotide phosphate oxidase 1 (NOX1) ( Zhang et al, 2021a ).…”
Section: Inhibition Of Ferroptosis Can Reduce Radiation Damagementioning
confidence: 99%
“…It is shown that NO• produced by macrophages inhibits PA-induced ferroptosis by inhibiting phospholipid peroxidation, especially the production of 15-HOO-AA-PE [76]. Meanwhile, PA generates proferroptotic signal 15-HOO-AA-PE through 15-pLoxA, which suggested that pLoxA inhibitors might be a promising treatment for PA infection [77]. Ferroptosis is a kind of cell death induced by iron-dependent oxidative stress [78].…”
Section: Bacterial Infectionmentioning
confidence: 99%